Comercialização e sazonalidade da produção pesqueira da pescada branca (Plagioscion squamosissimus) no município de Santarém, Pará, Brasil - COELHO, Alessandro Alves (Universidade Federal do Oeste do Pará, 2023)
Fishing is the basis of the economy in the Amazon Region, and this activity stands out in relation to other regions due to the richness of the exploited species and the quantity of fish caught annually. Besides fishing in the coastal region of the state, the river fishing in the region of the lower Amazon stands out. It is carried out by fishermen from the main cities of the region such as: Santarém, Óbidos, Monte Alegre, Alenquer, Prainha and Almeirim. The city of Santarém stands out in the scenario of fish purchases by companies in the Belém region. Among the main species landed to supply the local market is the Plagioscion squamosissimus, popularly known as hake. The present work aims to analyze the commercialization and seasonal variation of the white hake species in the municipality of Santarem, evaluating the regional production variation, in the seasonal regime, and to describe the commercialization stages of the intermediary, analyzing the fish processing strategies for sending the production for commercialization. The collection of information took place from March to December 2021 and March to December 2022. The follow-up was done from the arrival of the hake in the ports of the city to the entrance and exit, both in the slaughterhouses and the direct trip to Belém in refrigerated trucks. The sensorial analysis was used right at the landing and the more accentuated classification at the reception of the fish, where the standard is the release of the entry note of the quantity landed, both by weight and by classification. The fishing activity for the purchase of hake in the region of Santarem is a promising activity, because besides moving the purchase market, it moves the whole chain from the fisherman in the rivers and lakes of the region to the exit of the fish from the packing plants, generating work and employing people directly and indirectly